2012
DOI: 10.1177/0363546512458086
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Tunnel Measurements and the Quadrant Method Using Fluoroscopic Radiographs After Anterior Cruciate Ligament Reconstruction

Abstract: Measurements with good to excellent reliability can be used to evaluate ACL tunnel placement when ideal radiographic views are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…In the present study, the femoral condyle overlap method was shown to be highly reliable. Although not yet validated against other quantitative measurement methods, a similar strategy using 90% condyle-to-condyle overlap has previously been used [30]. Further, since the femoral condyle overlap method is used to specify which radiographs can be used to assess the position of the femoral tunnel in the sagittal plane, potential varus or valgus deviation would not affect the interpretation of the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the femoral condyle overlap method was shown to be highly reliable. Although not yet validated against other quantitative measurement methods, a similar strategy using 90% condyle-to-condyle overlap has previously been used [30]. Further, since the femoral condyle overlap method is used to specify which radiographs can be used to assess the position of the femoral tunnel in the sagittal plane, potential varus or valgus deviation would not affect the interpretation of the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The tibial tunnel was placed 7 mm anterior to the posterior cruciate ligament (PCL) and slightly medial and posterior to the inner edge of lateral meniscus. Studies have investigated the relationship between arthroscopic anatomic landmarks and postoperative radiological and functional outcomes 78…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate the effect of different-sized femurs on our investigation, the distance between the intended and achieved femoral ACL tunnels was modeled in 2 dimensions. The grid method of Bernard et al, 9,55 as applied to the fluoroscopic true lateral images, allowed each intended and achieved tunnel position to be defined as a percentage ratio of the sagittal diameter of the whole lateral condyle measured along the Blumensaat line ( X axis) and as a percentage of the maximum width of the femoral condyle perpendicular to the Blumensaat line ( Y axis) (Figure 5). The achieved and intended tunnel positions were measured by an independent observer (J.R.) who was blinded to the names of the surgeons, their tunnel localization strategy, and their viewing portal used.…”
Section: Methodsmentioning
confidence: 99%